Sabaheta Huskić's shop where the late Faruk Huskić had a pottery workshop/shop, Gračanica. - Richard Carlton (21436850) (2025)
Sabaheta Huskić's shop where the late Faruk Huskić had a pottery workshop/shop, Gračanica.